Seeking to identify causes on the debatable quality of Brazilian education (Research, Society and Development, 2023)
From the criticisms made to the quality of Brazilian education, this work was elaborated, which has as main objective to seek possible causes that are contributing to the low quality of Brazilian education. Therefore, there should also be no teaching without learning. The investigation was based on three questions: a. How are learning and teaching handled in the school environment by teachers and students? B. How are learning and teaching treated by researchers? ç. How are learning and teaching treated by education managers? To answer the first, two hundred and forty-two students and thirty-six teachers were consulted, about which word was most heard “teaching” or “learning”, the answers indicated teaching in two hundred and seventy-six and learning only two. To answer the second, keywords with teaching and learning were used and with these, published works were searched on Google. One hundred and eighty-five were identified, of which 80% researched teaching, 12.5% researched teaching and learning and only 7.7% of the sample deals with learning. In the laws that govern Brazilian education, in the LDB the word teaching appears one hundred and ninety times and the word learning seven times teaching and learning only once. In the BNCC, the word teaching appears five hundred and forty-two times, the word learning one hundred and thirty-four and the word teaching-learning only eleven times. This demonstrates that in addition to the legislation being mainly focused on teaching, the problem is aggravated by the fact that teaching and learning are apparently unlinked.